Translation as language contact: a multidimensional perspective of syntactic variation - Liu, Yanmeng (Frontiers in Language Sciences, 2026)
Translators produce translations via consistent contact with at least two languages. Contact with different languages is a main factor influencing language changes at all levels. However, quantitative exploration of syntactic variation in translation as a language contact event remains underexplored. This study explains translation changes through the lens of language contact and quantifies the influence of language contact on translation syntax in fiction and non-fiction genres. Univariate and multivariate analyses were conducted to examine linguistic variations at the syntactic level in Chinese-English translations by two groups of undergraduate student translators (Grade 4, with a higher degree of language contact; and Grade 3, with a lower degree), with expert translations serving as a benchmark for acceptable language changes. The results reveal four primary dimensions of syntactic variation: (1) structure diversity, (2) production length, (3) sentence complexity, and (4) information fragmentation. Genre-specific effects were observed, with translations in both genres exhibiting statistically significant syntactic changes across four dimensions, while fiction translation insignificant regarding the dimension of structure diversity. The findings imply that contact-induced linguistic changes amplify simplification and explicitation in translation, and manifest more prominently in genres oriented toward information transfer than in those prioritizing stylistic distinctiveness and immersive storytelling. These findings suggest that language contact offers a valuable lens for understanding linguistic changes in translation and imply that genre and language change mechanism are important factors in this perspective.